Proses Pembelajaran Deep Learning melalui Project Based Learning pada Pagelaran Tari “Nusantara Bercerita” di Kelas XII SMA Negeri 1 Sulang - Wahyu Nur Isnaini; Eny Kusumastuti (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
This research intends to investigate the process of deep learning by utilizing the Project-Based Learning (PjBL) framework during the dance performance initiative named “Nusantara Bercerita,” which took place in Grade XII at SMA Negeri 1 Sulang. A qualitative method was adopted, employing a descriptive case study design. The individuals involved in the research included the dance instructor and the students participating in the dance performance initiative. Information was gathered through methods such as observation, interviews, and documentation. To ensure the validity of the data, source triangulation, technique triangulation, member checking, and ongoing observation were utilized. Data examination was conducted via the processes of data minimization, data visualization, and drawing conclusions. The results suggest that the use of Project-Based Learning in dance instruction improves students' engagement, creativity, teamwork skills, communication skills, and self-assurance. Students were actively engaged in every stage of the project, including planning, concept development, movement and choreography exploration, rehearsals, and the final dance performance. Deep learning was reflected in students’ understanding of cultural values, reflective learning experiences, collaborative competencies, and creativity in producing dance works. This understanding was demonstrated by students' ability to explain the meaning of dance movements and relate them to the cultural values represented in the performance theme, rather than merely memorizing movement sequences. Although several challenges were encountered, such as a lack of discipline and coordination among group members, the project was successfully completed through effective communication and teamwork. Therefore, the implementation of a dance performance through Project-Based Learning provides an authentic and valuable learning experience, contextual, and experience-based learning environment.